Simultaneous Spectrophotometric Estimation and Validation of Domperidone, Tramadol Hydrochloride and Acetaminophen in Tablet Dosage Form - Jain, Vikas; Sharma, Rajesh (Stamford Journal of Pharmaceutical Sciences, 2011)
Simultaneous estimation of active ingredients in multi-component pharmaceutical products normally requires the use of separation techniques, such as HPLC, HPTLC or GC, followed by their quantitation. Presented here are two spectrophotometric methods that do not require prior separation for simultaneous estimation of three drugs; acetaminophen, tramadol hydrochloride and domperidone in a tablet formulation. Shimadzu UV 1700 capable of multi-component analysis was used for quantitation. Method A is based on the simultaneous equation and method B on the multi-component analysis. The absorption maxima of the drugs found to be at 244nm, 271.5nm and 284.5nm respectively for acetaminophen, tramadol hydrochloride and domperidone in methanol/0.1 N HCl (1:2) solvent mixture. Acetaminophen, tramadol hydrochloride and domperidone obeyed Beer's law in the concentration range of 2-22 μg/ml, 10-55 μg/ml and 30-300 μg/ml respectively. The simultaneous equation method is based on the additivity of absorbances and multi-component analysis involves recording of absorbances of standard solutions at 244nm, 250nm, 271.5nm and 284.5nm. These were processed by means of statistical calculations and results of sample solution were obtained. Result of analysis for both methods were tested and validated for various parameters according to ICH guidelines. Key Words: simultaneous equation method; multicomponent analysis; acetaminophen; tramadol hydrochloride; domperidone. DOI: 10.3329/sjps.v3i1.2655 S. J. Pharm. Sci. 3(1): 28-33